Analysis and diagnosis for 12 job level of training junior civil engineers in operations and structural engineer tasks - Faqih Ma'arif; Ahmed Wasiu Akande (Faculty of Engineering, Universitas Negeri Yogyakarta, 2023)
This study aims to determine the competencies of twelve job levels in housing construction work, as well as effective strategies to improve employee skills in each field. The method used is qualitative by conducting interviews in each competency field (infrastructure, structure, landscape, mechanical, and electrical). Closed questionnaires were carried out specifically for structural engineering work, which has a greater percentage of work than other fields. Education and training, as well as demonstrations through various learning media (modules, virtual reality, and tutorials), are carried out in parallel classes through an integrated schedule that the company has prepared. The results showed that in order to obtain a minimum standard of competence in all fields, 448 study hours were required with the details of the general manager, project manager, assistant manager, and supervisor, respectively, 38 JP, 120 JP, 160 JP, and 130 JP, which were divided into 45 subject areas. Analysis of the level of knowledge and skills reports that junior structure engineers need construction work assistance and standard knowledge about building construction compared to senior engineers who have exceeded the minimum passing criteria with an average achievement of 4.23 (84%) of the total material studied